Development of a framework on prohibition of adulterating surimi products with animal plasma: a qualitative research approach - Mohd Sukri, Siti Jamilah; Ahmad Fadzillah, Nurrulhidayah; Mat Jubri@Shamsuddin, Mustafa; Rohman, Abdul (Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2022)
The adulteration of commercial food products with muharramat (prohibited) ingredients exposes Muslims of the present time to food fraud. One of the muharramat sources is animal plasma food grade powder in surimi products. This adulteration using prohibited substance is regarded as a critical halal issue that should be addressed to strengthen the justification for its prohibited status. The current study employs a qualitative approach using semi-structured interview data with Shariah experts, Halal executives, and food technologists as the main source of data collection, and a literature review as supportive argument. The application of thematic analysis to analyze the collected data enabled the identification of the main themes and sub-themes of the interview data. Based on the results, the identified main themes are: the principles of Istihlak fasidah (imperfect transformation), Istishab (presumption of continuity), and Maslahah (preservation of public interest); while the identified several sub-themes are: the involvement of human intervention, the residual traces of animal plasma properties in/the end product, and the prohibition of spilled-out blood that is attributed to all of the blood components, as supportive arguments to justify the reasons for Istihlak fasidah (imperfect transformation) process. Last but not least, several principles of Qawaid Fiqhiyyah (Islamic Legal Maxim) become part of the identified sub-themes applied by the interviewees to enhance the prohibited status. Subsequently, a framework is presented to visually present the data to clarify the interrelatedness of the identified themes. The research findings can potentially contribute signigicant knowledge to the Contemporary Fiqh Consumerism field, particularly in understanding the issue of intentionally adulterating halal with non-halal sources. The developed framework also meets the criteria of future new research since no comprehensive study has been conducted to highlight the prohibition of using animal plasma in food products.